Retention in school: could student’s affective engagement play an essential role in its prevention? - Silva, Cláudia Ribeiro da (2022)
Introduction: In Portugal, the retention in school presents worrying figures. The indicator "Direct Paths to Success", created by the Ministry of Education, shows that the majority of students who did not finish secondary school in 2019 was because they failed a year or had a negative score in at least one of the national exams. Out of a universe of 456,368 students, only 201,937 (44%) had the so-called "direct success path". (Source: http://infoescolas.mec.pt/ 02/2019) Objetives: The main goal of this study is to inquire if the students who had been held back were the ones who showed at the beginning of the school year less emotional commitment in comparison with students that moved forward. Methods: The sample comprises 330 students from the 10th grade of a secondary school in Lisbon, and the data were collected using a scale proposed by Veiga (2013, 2014, 2016) – Student’s Engagement in School (EAE-E4D), at the end of the first school term. Results: Considerable differences emerged between the two groups in all the items of the affective dimension. The group retained had the worst results. Conclusion: The students’ affective engagement is crucial for academic success, and school should promote it through strategies that can provide their well-being and prevent retention.